Mais uma vez e apesar de tudo, o que pode uma educação - Almeida, Jefferson Pereira de (My University, 2025)
Developed in the Postgraduate Program in Education at the University of Caxias do Sul, in the History and Philosophy of Education research line, this doctoral study finds its first driving force in Freud's suspicion that there are impossible professions. Sown in fertile ground, the hypothesis of the impossibility of education emerges persuasively and creates the conditions for a research problem. Thus, we take a journey with Friedrich Nietzsche to think about the possibilities and limits of education, from his philosophical vocabulary. Other less obvious flows produce the movement. The redescription and critique of the conceptual elements of pedagogical thought is elaborated: accessing the metavocabulary, questioning its subject matter and intentions, identifying the forces that constitute it, claiming contingency, and estimating the impacts of these actions on the current way of thinking about education. By looking and being suspicious, the supposed privilege of words must be examined. In this ongoing attempt, it is important that conceptual creation comes into play through the fabrication of an education, an opportunity to experience its virtuality. At this point, the thought dares to leave Nietzsche, seeks out and traverses other references in contemporary philosophy, appropriates intercessors from literature, and acts affirmatively. Something rhizomatic affects the layout of the material, which also does not hide the taste for repetition and the predilection to return each time, always trying to tense the curvature of the circle. Each chapter is one more - bis, ter, quater, quinquies, sexies, septies, is repeated and yet little seems identical, there are plenty of relationships that want to be different. In the end, maybe the new will happen in et caetera. In this way, the writing integrates redescription and critique; one after the other, the reassuring categories are brought to light, confronted, twisted and twisted. Symptomatology is presented as reaction, avoidance, capture, stagnation of flow. Education is melancholic, it perseveres in memory and idealization, it remains fixed to the télos that would define it. As an active and plastic force, forgetfulness tries to serve as an antidote to melancholy, but it also generates adverse reactions, leaving the door ajar for the old categories to return, this time updated by the demands of the economy. Under capitalism, education is a functional process whose development prioritizes teaching and learning. However, something affirmative runs along the paths, something escapes and leaks out, sabotaging the order, shaking the intention of the center. In confronting the symptoms there is joy and laughter, play and dance, there is endless mediality and invisibility of gesture; the writing creates its own lines of escape and a certain Dionysian ambience thrives and sets the tone. Absolute diagnoses are uncomfortable, they suffer from idealism; it is uncomfortable to admit peremptory deaths, definitive disappearances, unappealable failures, ethical-political despairs. Impossibility is specified by circumstantial impotence; as dispersion in the midst of so much gibberish, impotence is reversible, circumventable, subverted, it makes us believe that in the interstices and openings there is an opportunity to frustrate domination. The experimentation carried out forges new conditions, fables an education that would be crossed by composition, by the creation of style. Education is not the path that leads from one place to another, it is not the point of articulation between past and future, the place where memory is actualized in the purpose of action, it does not establish models, it is not a promise of humanity. Education risks the outside, opens itself up to infinity and the productive unconscious, diagrams lines of escape; it is the becoming-animal, the disturbing production of an exit that escapes from humanity, that tensions it until it signals the inhuman. Finally, it is believed that the issue of what an education can be is answered when the normative criterion of morality is replaced by the ethical and political experimentation of desire in collective agency, in the micro-political experience of multiplicity and difference, in the joyful attempt to produce the common. [resumo fornecido pelo autor]
Desenvolvido junto ao Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul, na linha de pesquisa História e Filosofia da Educação, o estudo de doutoramento tem seu primeiro motor na suspeita freudiana de que existiriam ofícios impossíveis. Semeada em terreno fértil, a hipótese da impossibilidade da educação surge com persuasão e cria as condições de um problema de pesquisa. Assim, faz-se uma travessia com Friedrich Nietzsche para realizar um pensamento das possibilidades e dos limites da educação, de seu vocabulário filosófico. Outros fluxos menos evidentes produzem o movimento. Elabora-se a redescrição e a crítica dos elementos conceituais do pensamento pedagógico: acessar o metavocabulário, questioná-lo em sua matéria e em suas intencionalidades, divisar as forças que as constituem, reivindicar a contingência e estimar os impactos dessas ações na atual forma de pensar a educação. No olhar e na suspeita, debruçar-se, pois, sobre o pretenso privilégio das palavras. Na tentativa que se estende, é importante que a criação conceitual entre em funcionamento pela fabulação de uma educação, oportunidade em que se experimenta sua virtualidade. Nesse momento, o pensamento ousa sair de Nietzsche, procura e atravessa outros referenciais da filosofia contemporânea, apropria-se de intercessores da literatura e age afirmativamente. Algo de rizomático afeta a disposição da matéria, que também não esconde o gosto pela repetição e a predileção de retornar a cada vez, sempre experimentando tensionar a curvatura do círculo. Cada capítulo é mais uma vez - bis, ter, quater, quinquies, sexies, septies, repete-se e, ainda assim, pouco parece idêntico, abundam relações que se querem diferenciais. Ao cabo, quem sabe o novo aconteça no et caetera. Desse modo, a escritura integra redescrição e crítica; uma após a outra, as categorias tranquilizadoras são trazidas à mostra, confrontadas, torcidas e retorcidas. A sintomatologia é apresentada como reação, evitação, captura, estagnação de fluxo. A educação é melancólica, persevera na memória e na idealização, mantém-se fixada ao télos que a definiria. Como força ativa e plástica, o esquecimento tenta servir de antídoto à melancolia, mas também gera reações adversas, deixa a porta entreaberta para retornarem as velhas categorias desta feita atualizadas pelas exigências da economia. Sob o capitalismo, a educação é um processo funcional em cujo desenvolvimento se priorizam o ensino e a aprendizagem. No entanto, algo de afirmativo percorre as veredas, algo escapa e vaza, sabotando a ordem, sacudindo a intenção de centro. No enfrentamento dos sintomas há alegria e riso, brincadeira e dança, há medialidade sem fim e invisibilidade do gesto; a escritura cria suas próprias linhas de fuga e certa ambientação dionisíaca prospera e dá o tom. Constrange diagnósticos absolutos, eles padecem de idealismo, desconforta admitir mortes peremptórias, desaparecimentos definitivos, fracassos inapeláveis, desesperos ético-políticos. Especifica-se a impossibilidade pela circunstancial impotência; como dispersão no meio de tanta algaravia, a impotência é reversível, contornável, subvertida, faz acreditar que nos interstícios e aberturas existe a oportunidade de frustrar o domínio. A experimentação realizada forja novas condições, fabula uma educação que seria atravessada pela composição, pela criação de estilo. A educação não é o caminho que leva de um lugar a outro, não é o ponto de articulação entre passado e futuro, lugar onde a memória se vê atualizada na finalidade da ação, ela não institui modelos, não é promessa de humanidade. A educação arrisca o fora, abre-se à infinitude e ao inconsciente produtivo, diagrama linhas de fuga; ela é devir-animal, a inquietante produção de saída que escapa da humanidade, que a tensiona até que assinale o inumano. Finalmente, acredita-se que a questão sobre o que pode uma educação esteja atendida quando se substitui o critério normativo da moral pela experimentação ética e política do desejo em agenciamento coletivo, na experiência micropolítica da multiplicidade e da diferença, na alegre tentativa de produção do comum. [resumo fornecido pelo autor]
Keywords: Educação - Filosofia; Education - Philosophy